2010
DOI: 10.1007/s10340-010-0343-0
|View full text |Cite
|
Sign up to set email alerts
|

Hyptis suaveolens and Hyptis spicigera (Lamiaceae) essential oils: qualitative analysis, contact toxicity and repellent activity against Sitophilus granarius (L.) (Coleoptera: Dryophthoridae)

Abstract: Essential oils from Hyptis suaveolens (L.) Poiteau (Lamiaceae) and Hyptis spicigera Lamarck (Lamiaceae) were first analysed by gas chromatography and by gas chromatography/electron impact mass spectroscopy and then evaluated for toxicity and repellent activity against Sitophilus granarius (L.) (Coleoptera: Dryophthoridae), one of the most serious worldwide stored grain pests. Fifty-six compounds have been identified in the essential oil of H. suaveolens: monoterpene hydrocarbons were the most represented volat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
29
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 26 publications
5
29
0
Order By: Relevance
“…Thus, in present bioassay exposure period is considered to be most important factor affecting the toxic effects of the vapor of essential oils to a certain extent than the dosage. The present findings are supported by Conti et al 22 and indicate that insecticidal mode of action of the studied essential oil largely attributed to their fumigant action and found to be toxic by penetrating the insect body via respiratory system. Plant products inter into the tissue and organ of target insects and affect the activity of various detoxifying enzymes 23 .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Thus, in present bioassay exposure period is considered to be most important factor affecting the toxic effects of the vapor of essential oils to a certain extent than the dosage. The present findings are supported by Conti et al 22 and indicate that insecticidal mode of action of the studied essential oil largely attributed to their fumigant action and found to be toxic by penetrating the insect body via respiratory system. Plant products inter into the tissue and organ of target insects and affect the activity of various detoxifying enzymes 23 .…”
Section: Discussionsupporting
confidence: 89%
“…Othira et al 21 reported that essential oil of Hyptis spicigera exhibited strong insect repellent activity at lower dosage against Sitophilus zeamais Motsch and T. castaneum and it was not significantly influenced by increase in the concentration of oil. On the contrary, Conti et al 22 reported that the essential oil of Hyptis spicigera exhibited a higher repellent effect in comparison to H. suaveolens against Sitophilus granarius and by increasing the dose of the oil the repellent activity was found to be increased. Similarly, in the present study all the dosage of TNG oil exhibited higher repellent activity than TNM and TNB essential oil samples and repellency increased with increasing oil concentration.…”
Section: Discussionmentioning
confidence: 94%
“…Lamiaceae species of the Hyptis genus-which included more than 400 species-are highly aromatic and grow in tropical regions, mainly in Africa and America. Several studies have shown that Hyptis suaveolens (L.) Poiteau EO has useful insecticidal properties against mosquitoes (Amusan et al 2005;Jaenson et al 2006) and many stored products pests (Peerzada 1997;Othira et al 2009;Conti et al 2011). Moreover, its chemical composition and biological activity change as a function of plants origin and their collecting period (Tchoumbougang et al 2005;Noudjou et al 2007).…”
Section: Introductionmentioning
confidence: 95%
“…In recent years, essential oils (EOs) of aromatic plants, characterized by low toxicity to mammalians and already extensively used in the food industries as supplements, and flavoring compounds, received a great attention as pest control agents due to their insecticidal, repellent, and/or antifeedant properties (Isman, 2006;Nerio et al, 2010;Conti et al, 2010Conti et al, , 2011Benelli et al, 2012). As a consequence, aromatic plants are studied as potential sources of repellents and insecticides (Nerio et al, 2010;Shaaya and Kostyukovysky, 2006;Conti et al, 2010;Caballero-Gallardo et al, 2012;Olivero-Verbel et al, 2013).…”
Section: Introductionmentioning
confidence: 98%